Correspondence between electronic structure calculations and simulations: nonadiabatic dynamics in CS2. Issue 26 (12th December 2018) - Bellshaw, Darren; Minns, Russell S.; Kirrander, Adam
Abstract : The choice of ab initio electronic structure method is an important factor in determining the fidelity of nonadiabatic dynamics simulations. Abstract : The choice of ab initio electronic structure method is an important factor in determining the fidelity of nonadiabatic dynamics simulations. We present an in-depth comparison of two simulations of photodissociation in the CS2 molecule following excitation to the 1 1 B2 state. The simulations account for nonadiabatic and spin–orbit coupling, and are performed using the SHARC surface-hopping approach combined with state-averaged SA8-CASSCF(8, 6)/SVP and SA8-CASSCF(10, 8)/SVP ab initio calculations, with additional reference calculations at the MRCI(14, 10)/aug-cc-pvTZ level. The relative performance and veracity of the simulations can be assessed by inspection of the potential energy curves along specific coordinates. The simulations demonstrate direct competition between internal conversion and intersystem crossing, with strong correlation between molecular geometry, electronic state density, and dynamics.